(3JQJjH GdSdhc Edi edc Gdedhcs - (3HMQb , SQGL GdOjf eMeO Hf YeQ Hf eHGQc GdMejQj GdMVQej, HMQb,J (B930 (3g` s ((3QVhGf Hf CMeO Hf YHO GdQMef Hf CMeO HGQVhGf HGaVd s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO agPg fHPg ai JQJjH GdSdhc Ydi edc Gdedhc Ld hYdG , eTJedI Ydi ebOeI hKdGKI aUd hNGJeI s
(3BNQgG (B:s
(3hgh ebGe GdEMSGf hgh BNQ SjQ GdeQjO hjHJOi ai GdSaQ ai Gddg Ci ai eYQaI Gddg Je cJGH JQJjH GdSdhc s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3bQFJ Ydi eMeO Hf YHO GdQMef Hf GdMSjf GdMOGO SfI (B1236(3g` hbQFJ CjVkG Ydi GdMSjf Hf UGdM GdHMQ GdLYaQi SfI (B1248s
(3YdjgG JbjjOGJ s
(3cJH HYV cdeGJgG HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdadSaI hGdefWbs